No reason for murder - Sono, Ayako. 1931-; Putzar, Edward (New York : ICG Muse Inc., 2003)
'Set on the rural Miura peninsula, southwest of Tokyo, the story focuses on the relationship between two very different people: Yukio, a humble, single Christian woman with strong principles; and Fujio, an undisciplined social misfit and womanizer who loathes the social mores of his fellow human beings. Yukio turns out to be the one woman Fujio cannot seduce, and she provides a moral lifeline for his confused psychological state as he sinks ever further into a mire of rape, murder and incarceration.'--dust jacket.
Keywords: Detective and mystery stories, Japanese; Suspense fiction -- Japan